Kinetic and adsorption study of Pb (II) toward different treated activated carbons derived from olive cake wastes. Issue 18 (14th April 2016) - El-Kady, Ahmed A.; Carleer, Robert; Yperman, Jan; D'Haen, Jan; Abdel Ghafar, Hany H.
Abstract: Adsorption capacity of activated carbons (ACs) derived from olive cake toward Pb (II) was tested in batch single ion experimental mode as a function of time, pH, carbon dose, and initial ion concentration. Physicochemical properties were carried out for produced ACs and a commercial Organosorb 10-CO to elucidate the variations of observed results. The total pore volume reached 0.676 cm 3 g −1 for AC2 (activated under forced air); however, AC1 (activated under nitrogen) and Organosorb 10-CO had almost similar total pore volume (0.448 and 0.432 cm 3 g −1, respectively). The mesopore volume for AC2 was 2.5 and 50 times of AC1 and Organosorb 10-CO, respectively. The scanning electron microscope images reflect the enhancement of thermochemical activation by H3 PO4 in increasing the porosity of both ACs. The adsorption of lead ions onto the ACs (confirmed by energy dispersive X-ray) occurred rapidly, since 45 and 48% of lead ions were adsorbed within 30 min onto AC1 and AC2, respectively, in contrast to a limited uptake for Organosorb 10-CO (27%). The q max was achieved within 2 h for AC1 and AC2; however, 3 h was required for Organosorb 10-CO. The tablet form of the commercial AC performs much slower in lead adsorption but established a much higher lead removal percent than the granular form. Langmuir isotherm provided the best fit to the equilibrium data with maximum adsorption capacity of 58.14, 188.67, and 39.84 mg g −1 for AC1, AC2, and Organosorb 10-CO, respectively. The sorption energy ( E -value) was 19.36, 8.92, and 11.48 kJ mol −1 for AC1, AC2, and Organosorb 10-CO, respectively, which indicated that the adsorption process takes physically place.